Influência da sinvastatina na reparação óssea de mandíbulas da ratas ovariectomizadas e nos níveis de colesterol sanguíneo - Junqueira, Juliana Campos [UNESP] (2001)
The purpose of this study was to evaluate the effects of the simvastatin on guided bone regeneration of mandibles of ovariectomized rats and to observe the blood cholesterol level in these animais, 70female rats were divided into four groups; normal control, ovariectomized control, normal treated and ovariectomized treated. A month after the ovariectomy a bone defect was created in the mandible, which was covered by a polytetrafluoroethylene membrane. Immediately after surgery the treated groups received 20 mg/K/day of simvastatin orally for 15 or 30 days. The rats were sacrificed 15, 30 and 60 days after the surgery, a blood sample was extracted to observe the cholesterol levels and the mandible was extracted to densiometric, histological and morphometric analyses. All specimens were submitted to analysis of variance (ANOVA) and to Tukey's method. The ovariectomized groups presented higher cholesterol level than the treated normal group and no significant statistical difference was found between the different treatment periods and the sacrifice times. The densiometric, histological and morphometric analyses showed that the treated ovariectomized group presented more quantity of new bone formation when compared to the control ovariectomized, but no statistica1 difference was observed between the treatment periods. It can be concluded that the deficienty of estrogen increased the level of blood cholesterol and that the simvastatin helped the new bone formation in the ovariectomized animals